Early childhood caries in 1-5 year-old children. Medellín, Colombia, 2008 - Ramírez-Puerta, Blanca Susana; Escobar-Paucar, Gloria; Franco-Cortés, Ángela María; Martínez-Pabón, María Cecilia; Gómez-Urrea, Liliana (Revista Facultad de Odontología Universidad de Antioquia, 2011)
Introduction: the purpose of this study was to estimate the experience, prevalence and severity of dental caries in 1-5 year-old children attending day care centers in a low and middle-low socioeconomic area. Methods: 659 children who were attending day care centers in the North Eastern area of the city of Medellin were examined. A calibrated (intra examiner Kappa 0.77 and inter examiner 0.71) examiner registered dental caries lesions, using International Caries Assessment and Detection System (ICDAS) criteria. Dental caries experience was calculated according to age, gender and distribution levels of severity. Results: using ICDAS criteria, 69.7% of children had early childhood caries (ECC), the average affected surfaces was 5.12 (±7.5), with significant differences by age and predominance of early lesions in 1-3 year-old children. Conclusion: the population studied had high levels of dental caries, reflecting that it is still necessary to advance in the definition of oral health policies for young children in the city.